A study of the patients' waiting time at the pharmacy counter, Hospital Kulim - Baharudin, Mohd Faizal; Agus Salim, Nurfariza Aras (2009)
The purpose of this study is to identify patient waiting time and to investigate the factors that contribute to the interruption of waiting time, it's related to the National Pharmacy charter of waiting time stated that more than 90% of the prescription should be dispenses within 30minutes. An observational retrospectively study was carried out in outpatient pharmacy department in Kulim Hospital. From the total 21,562 prescription, 11,000 were included in this study. Data were collected through Queue Management System (QMS) where it states patient's arrival and dispense time. Result shows that more than 97% of the prescriptions were dispensed in less than 30 minutes, and other 3% was delayed. There are factors that can leads to the delay such as long list of prescription, wrong dosage, insufficient counters for dispensing process and many more. The patients' waiting time issue should not be take seriously by the hospital but the patients satisfaction is very important thing to make sure the services given is the best. Besides, delay in waiting time may lead to poor patients' compliance. So that our attention is necessary, therefore be made to overcome the delay of waiting time.